Delhi Transport Department : case of Uber taxi rape - Raghuram, G., 1955- (London : SAGE Publications Ltd, 2017)
This case describes the events following an incident of a rape in a taxi associated with Uber, by its driver. Uber was an application based taxi operator. The events raised several issues for government systems and processes, such as need for regulation of new formats of business like application based taxi services, integrated databases, checks against forgery and holistic approach towards women safety. The case also brings out how an e-commerce business raises regulatory concerns.
Originally published: Raghuram, G. (2015). Delhi Transport Department: case of Uber taxi rape. PSG0119. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Delhi (India : Union Territory). -- Department of Transport; Uber; Taxicab drivers -- India -- Delhi Metropolitan Area; Rape -- India -- Delhi Metropolitan Area -- Case studies; Rape victims -- India -- Delhi Metropolitan Area -- Case studies